The Urban Environmental System perspective on socio-environmental risks of urban flooding - Farias, Ariadne; Mendonça, Francisco (Sociedade & Natureza, 2022)
In the context of urban socio-environmental problems, floods stand out due to the amplitude of their impacts on built spaces and populations’ lives. This problem has become an object of study in several knowledge areas, particularly from an interdisciplinary perspective, applied to understand and identify risks and socio-environmental vulnerabilities associated with hydrological disasters. The occurrence of extreme precipitation events registered in Brazilian cities has also drawn the attention of both public managers and agents since, every year, urban river floods cause severe damage to the population and services located in risk areas. Overall, floods in large, medium-sized, and even small cities are related to land use and land cover, as well as to rainwater management in urban spaces. Driven by these issues, this study presents results regarding the socio-environmental risks of urban flooding in Francisco Beltrão, a town located in Paraná State – Southern Brazil. It is based on the Urban Environmental System (UES) methodology, which is applied to identify social and environmental factors that intervene in the production of risks and vulnerabilities related to hydrological disasters. In the social subsystem domain, material losses related to urban flooding in Francisco Beltrão evidence the vulnerabilities of the affected population and the economic and social damage. On the other hand, regarding the natural subsystem domain, there is an increased hazard of extreme hydrometeorological events, which might lead to river flooding. Considering the urban socio-environmental system of Francisco Beltrão, the population's exposure to the flood hazard and the environmental degradation of urban rivers points to the use and occupation of risk areas.